Analysis of the Implementation of Stunting Prevention Policies in North Tapanuli Regency - Naomi F. Aritonang; Donal Nababan; Laura M. Siregar (Jurnal Info Sains : Informatika dan Sains, 2023)
This study discusses the issue of stunting in Indonesia, particularly in the Tapanuli Utara District. Indonesia, with its vast population, faces fundamental health challenges, including stunting resulting from malnutrition in toddlers. The research indicates that the rate of stunting in Indonesia surpasses the threshold set by the WHO, especially in areas with high poverty and low education levels. The primary objective of this research is to understand the implementation of stunting prevention policies in the Tapanuli Utara District. The study adopts a qualitative approach using a phenomenological research design. Data collection was carried out through in-depth interviews, observations, and documentation. Findings from this study show that even though various stunting intervention programs have been implemented, there remain obstacles in their application. A primary factor is the community's lack of knowledge about the significance of the stunting issue and the perception that stunting is caused by hereditary or genetic factors. Policies at the national and provincial levels have been developed to address this issue, but their implementation at the district level requires stronger coordination among various stakeholders. In conclusion, despite ongoing efforts to address the stunting problem in Indonesia, a more integrated and holistic approach is still needed, as well as increased community awareness of the issue.